Synthesis and fabrication of superstrate and substrate Cu2ZnSnS4/CdS thin film solar cells utilizing copper powder as local materials - Eka Cahya Prima; Anggi Datiatur Rahmat; Andhy Setiawan (Universitas Ahmad Dahlan, 2023)
Cu2ZnSnS4 is a promising material for low-cost thin-film solar cells. This paper reports a new approach to fabricating a solar cell using a Superstrate and Substrate configuration. We utilized a non-vacuum deposition process to deposit Copper Zinc Tin Sulfate (CZTS) and Cadmium Sulphate (CdS) on a glass substrate. To achieve this, we adopted the sol-gel spin coating method for CZTS and the Chemical Bath Deposition (CBD) method for the CdS layer. The solar cell has two structures: ITO/Cu2ZnSnS4/CdS/Ag for substrate configuration and ITO/CdS/Cu2ZnSnS4/Ag for superstrate configuration. The Cu/(Zn+Sn) atomic ratio was set to 0.86, while Zn/Sn was set to 1.25. Our CZTS/CdS solar cell achieved a 48.7 × 10-6 % power conversion efficiency with a 1.40 eV band gap and 98.71 % external quantum efficiency at 373 nm for the superstrate configuration. For the substrate configuration, the power conversion efficiency was 19.0 × 10-6 % with a 1.49 eV bandgap and 95.74 % external quantum efficiency at 321 nm. Based on the results presented in the text, the CZTS solar cell with a superstrate configuration achieved a higher power conversion efficiency and external quantum efficiency than the substrate configuration. The superstrate configuration allowed for better light absorption in the CZTS layer and reduced the reflection of light back into the substrate. This configuration also prevented the back diffusion of CdS into CZTS and improved the electrical performance of the solar cell. Therefore, the superstrate configuration is more efficient than the substrate configuration for CZTS solar cells.